ELECTRICAL RESISTIVITY OF ALLOYS Sn-Pb - Medrano Atencio, Emilio (2000)
Alloys of Sn-Pb have been obtained by the fussion method with concentrations of lead in tin from 0% to 100%. The electrical resistivity of the samples has been measured at room temperature. The results of these measurements are reported and are interpreted within the framework of the theory of electrical conductivity in metals.